If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 19 = -9 + -6x Reorder the terms: 19 + 4x = -9 + -6x Solving 19 + 4x = -9 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. 19 + 4x + 6x = -9 + -6x + 6x Combine like terms: 4x + 6x = 10x 19 + 10x = -9 + -6x + 6x Combine like terms: -6x + 6x = 0 19 + 10x = -9 + 0 19 + 10x = -9 Add '-19' to each side of the equation. 19 + -19 + 10x = -9 + -19 Combine like terms: 19 + -19 = 0 0 + 10x = -9 + -19 10x = -9 + -19 Combine like terms: -9 + -19 = -28 10x = -28 Divide each side by '10'. x = -2.8 Simplifying x = -2.8
| x+5=7x+2 | | 25-(-5)-7= | | 3x-22+65=180 | | 5=18a | | 3+x-4=7x-2 | | 2u^2+3u-20=0 | | 4*x+3=2(2x+9) | | (x-8)=x-3 | | 6+2(2-4x)=6x+2(2x-4) | | 30+40x=35 | | 55=285-10e | | 2(6x+10y)+8=0 | | 4(x-6)-10=2x | | b=11-a | | 2(x-4)-6=-6(-2x+4)-6x | | 6r+5=55 | | k+3=6+k | | 30+(.0825*30)+(15%*30)= | | 6(y+2)=-2(8y-7)+6y | | -26+26=-15p-10p | | 11x-4=5x+9 | | x*12=-2 | | X+3(4)=48 | | 3x+10=3x+4+1 | | 2(x-1)-3x=8 | | 8-2x=2x-5x | | 1x+3(4)=48 | | 9(-10)+160= | | -6h+2=-46 | | x+7=-3+3x | | .60x+.30(90)=.50(x+90) | | 6=18b |